Semi-analytic models and background hydrogen-ionizing flux - Devriendt, J; Guiderdoni, B; Sethi, S (1999)
We estimate the contribution of galaxies to the cosmic background flux at 912 Angstrom by means of an extended semi-analytic model of galaxy formation and evolution which takes into account the absorption of Lyman-limit photons by HI and dust in the interstellar medium (ISM) of the galaxies. We find that, though the background Lyman-limit flux escaping from galaxies is negligible compared to the flux from quasars at high redshifts, these two contributions become comparable at z similar or equal to 0.